Auricular acupuncture for prehypertension and stage 1 hypertension: study protocol for a pilot multicentre randomised controlled trial - Kim, Joo-Hee (BioMed Central, 2013)
BACKGROUND: Hypertension, a worldwide public health problem, is a major risk factor for cardiovascular and kidney disease, and the medical and economic burden of hypertension is increasing. Auricular acupuncture has been used to treat various diseases, including hypertension. Several studies have shown that auricular acupuncture treatment decreases blood pressure in patients with hypertension; however, the scientific evidence is still insufficient. Therefore, we aimed to perform a randomised controlled clinical trial in patients with prehypertension and stage 1 hypertension to evaluate the effect and safety of auricular acupuncture. METHODS/DESIGNS: This on-going study is a two parallel arm, assessor-blinded, randomised controlled trial. Sixty participants with prehypertension and stage 1 hypertension will be recruited and randomly allocated into two groups in a 1:1 ratio. Participants in the auricular acupuncture group will receive auricular acupuncture treatment two times per week for 4 weeks. Participants in the usual care group will not receive any acupuncture treatment during the study period. All participants in both groups will be provided with verbal and written educational materials regarding the dietary and physical activity habits for controlling high blood pressure, and they will self-manage their lifestyle, including diet and exercise, during the study. The primary outcome is the 24-h average systolic and diastolic blood pressure, as measured with an ambulatory monitor. The secondary outcomes are the mean change in the average systolic and diastolic blood pressure during day- and night-time, the circadian rhythm of blood pressure, the mean arterial pressure, the change in blood pressure before and after auricular acupuncture treatment, the EuroQOL-5D (EQ-5D), heart rate variability (HRV), body mass index (BMI) and laboratory examination, including lipid profile and high sensitivity C-reactive protein (hs-CRP). Safety will be assessed at every visit. DISCUSSION: This pilot multicentre randomised controlled trial will explore the feasibility of further auricular acupuncture research and provide important clinical evidence for the effect and safety of auricular acupuncture on blood pressure in patients with prehypertension and stage 1 hypertension compared with usual care. TRIAL REGISTRATION: Clinical Research Information Service: KCT0000169